Measurement of secondary radiation during ion beam therapy with the pixel detector Timepix - Martišíková, Mária; Jakubek, Jan; Granja, Carlos; Hartmann, Bernadette; Opálka, Lukáš; Pospíšil, Stanislav; Jäkel, Oliver (Journal of Instrumentation, 2011)
In ion beam therapy the finite range of the ion beams in tissue and the presence of the Bragg-peak are exploited. Unpredictable changes in the patient`s condition can alter the range of the ion beam in the body. Therefore it is desired to verify the actual ion range during the treatment, preferably in a non-invasive way. Positron emission tomography (PET) has been used successfully to monitor the applied dose distributions. This method however suffers from limited applicability and low detection efficiency. In order to increase the detection efficiency and to decrease the uncertainties, in this study we investigate the possibility to measure secondary charged particles emerging from the patient during irradiation. An initial experimental study to register the particle radiation coming out of a patient phantom during the therapy was performed at the Heidelberg Ion Beam Therapy Center (HIT) in Germany. A static narrowly-focused beam of carbon ions was directed into a head phantom. The emerging secondary radiation was measured with the position-sensitive Timepix detector outside of the phantom. The detector, developed by the Medipix Collaboration, consists of a silicon sensor bump bonded to a pixelated readout chip (256 × 256 pixels with 55 μm pitch). Together with the USB-based readout interface, Timepix can operate as an active nuclear emulsion registering single particles online with 2D-track visualization. In this contribution we measured the signal behind the head phantom and investigated its dependence on the beam energy (corresponding to beam range in water 2-30 cm). Furthermore, the response was measured at four angles between 0 and 90 degrees. At all investigated energies some signal was registered. Its pattern corresponds to ions. Differences in the total amount of signal for different beam energies were observed. The time-structure of the signal is correlated with that of the incoming beam, showing that we register products of prompt processes. Such measurements are less likely to be influenced by biological washout processes than the signal registered by the PET technique, coming from decays of beam-induced radioactive nuclei. This work demonstrates that the Timepix detector is able to register ions emerging from the patient during the treatment by carbon ion beams. In future work it will be investigated which information about the incoming beam can be gained from the analysis of the measured data.